2004
DOI: 10.1086/425878
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeNICMOS Variability Study of Massive Stars in the Young Dense Galactic Starburst NGC 3603

Abstract: We have used the relatively long data string of the 1997-1999 NICMOS focus tests on NGC 3603 to extract $J-band light curves for several hundred stars in the cluster core. Given the relatively modest photometric precision [(J ) ! 0:05 mag], we were able to isolate only a half-dozen variable candidates with peak-to-valley amplitudes above $0.2 mag. One of the variables is one of the two outstandingly brightest cluster members, A1, located in the very dense cluster center. A1 shows double eclipses on each orbita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 20 publications
(32 reference statements)
4
42
2
Order By: Relevance
“…Without such high spatial resolution, this would have been impossible in the tight core of NGC 3603. Schnurr et al's spectra confirm the binary nature of star A1 (with two unequally bright WN stars), for which deep double eclipses in a P = 3.7724d orbit were found previously from HST/NICMOS photometry (Moffat et al 2004), leading to an orbital inclination i = 71 o . Combined with the RV orbits, this yields masses of 114±30 and 84±15 M for A1.…”
Section: Ngc 3603/a1 Csupporting
confidence: 70%
“…Without such high spatial resolution, this would have been impossible in the tight core of NGC 3603. Schnurr et al's spectra confirm the binary nature of star A1 (with two unequally bright WN stars), for which deep double eclipses in a P = 3.7724d orbit were found previously from HST/NICMOS photometry (Moffat et al 2004), leading to an orbital inclination i = 71 o . Combined with the RV orbits, this yields masses of 114±30 and 84±15 M for A1.…”
Section: Ngc 3603/a1 Csupporting
confidence: 70%
“…-Two additional examples of very massive stars in elliptical orbits whose large eccentricity made the discovery of their binarity difficult are WR 22 ≡ HD 92 740 (Moffat & Seggewiss 1978;Conti et al 1979;Schweickhardt et al 1999, WN7 + O8-9.5 III:) and HD 93 162 (Gamen et al 2008;Sota et al 2014, O2.5 If*/WN6 + OB). -There are also very massive twin systems in shorter, nearcircular orbits such as NGC 3603-A1 (Moffat et al 2004;Schnurr et al 2008, WN6ha + WN6ha), WR 20a (Rauw et al 2004;Bonanos et al 2004;Crowther & Walborn 2011 we note that σ Ori B is B0.5 V). Why were these systems not discovered earlier?…”
Section: Discussionmentioning
confidence: 65%
“…Based on HST NICMOS data, Moffat et al (2004) suggested that A1 is possibly an eclipsing binary system with a 30Y90 M H-rich WR component ( WN6ha) and a 25Y50 M O star companion. The source B also has been suggested to be a binary system (e.g., Moffat 1983).…”
Section: Main-sequence Starsmentioning
confidence: 99%